2022
DOI: 10.3389/fonc.2022.924061
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of H3K27cr Modification During DNA Damage in Colon Cancer

Abstract: DNA damage plays an essential role in the initiation and development of colon cancer. Histone crotonylation is a newly discovered post-translational modification that is thought to promote gene expression. Whether histone crotonylation plays a role in DNA damage of cancer remains unknown, as does the putative underlying molecular mechanism. This study aimed to investigate the relationship between histone crotonylation and DNA damage of colon cancer using multiple bioinformatics analysis and western blotting. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hou et al reported ENO1 regulates colorectal cancer through crotonylation ( Hou et al, 2021a ). Liao M et al reported the relationship between histone H3K27 crotonylation and DNA damage of colon cancer ( Liao et al, 2022 ). Qu M et al revealed a novel mechanism of histone crotonylation-mediated ATX expression regulation by in a HIF-2α-dependent manner in a colon cancer SW480 cells ( Qu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al reported ENO1 regulates colorectal cancer through crotonylation ( Hou et al, 2021a ). Liao M et al reported the relationship between histone H3K27 crotonylation and DNA damage of colon cancer ( Liao et al, 2022 ). Qu M et al revealed a novel mechanism of histone crotonylation-mediated ATX expression regulation by in a HIF-2α-dependent manner in a colon cancer SW480 cells ( Qu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qu ( Qu et al, 2023 ) et al reported that p300/CBP-mediated Kcr plays a role in the induction of hypoxia by ATX in SW480 cells. Liao ( Liao et al, 2022 ) et al reported a decrease in the level of H3K27cr, which may be facilitated by SIRT6 during DNA damage in colon cancer. However, whether p53 is capable of regulating the crotonylation of nonhistone proteins, subsequently contributing to cisplatin resistance, as well as the identity of the regulators and the specific crotonylation sites on p53-targeted proteins, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, at present, the effect of histone crotonylation on CRC progress has not been very clearly elucidated. Our previous findings revealed that the level of H3K27cr is significantly lowered during DNA damage in HCT116 cells [ 14 ]. Considering the strong association between DNA damage and CRC metastasis, H3K27cr could play a key role in CRC metastasis.…”
Section: Introductionmentioning
confidence: 99%